1999
DOI: 10.1007/s002160051183
|View full text |Cite
|
Sign up to set email alerts
|

Preconcentration of trace elements in sea water with poly (acrylaminophosphonic - dithiocarbamate) chelating fiber for their determination by inductively coupled plasma mass spectrometry

Abstract: A new ion exchange chelating fiber with aminophosphonic and dithiocarbamate groups based on polyacrylonitrile was used for the simultaneous preconcentration of beryllium, bismuth, cobalt, gallium, silver, lead, cadium, copper, manganese and indium in sea water. The optimum experimental parameters, such as fiber capacity, pH, sample flow rate and volume, eluant and effect of matrix ions on the preconcentration were investigated. The separation of analytes can be achieved from sea water with a concentration fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In our previous work, poly(acrylaminophosphonic dithiocarbamate) chelating fiber was developed and used to preconcentrate trace elements from seawater [2,19]. The synthesis was, however, time-consuming -approximately four days.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, poly(acrylaminophosphonic dithiocarbamate) chelating fiber was developed and used to preconcentrate trace elements from seawater [2,19]. The synthesis was, however, time-consuming -approximately four days.…”
Section: Introductionmentioning
confidence: 99%
“…Figures 6 and 7 show the effects of initial concentration (5,10,20,30, and 40 mg/L solutions) of the metal ions uptake onto the polymers. The results indicated that the most suitable metal concentration for maximum recovery of both metal ions was 5 mg/L.…”
Section: The Effect Of Initial Concentration On Adsorptionmentioning
confidence: 99%
“…3,4 In recent years, selective metal ion removal has been widely carried out using specific ligand-modified polymers for the preconcentration of some toxic metal ions. [5][6][7][8][9][10] Some organic polymer sorbents such as Amberlite XAD, Separon, and Polysorb are well known from the literature. 11 Recently, styrenedivinylbenzene-based insoluble resins (e.g., Lewatit), gelatinous and macroporous copolymers, and crosslinked polymer adsorbents gained vital importance because of their ability to remove high quantities of ions.…”
Section: Introductionmentioning
confidence: 99%
“…Amberlite XAD-2 was modified by different chelating agents such as o-vanilline thiosemicarbazone [23], dimethylglyoxal bis(4-phenyl-3-thio-semicarbazone), salicylic acid [24], alizarin red-S [25], aminophosphonic or dithiocarbamate group containing polyacrylonitrile [26].…”
Section: Introductionmentioning
confidence: 99%